Comparative study of biogas yield from animal manure in barn and farm - MohammedMuetaz - Boghandora Sulaiman- HassanRazena- JirhimanAbraheem- Ahmeedah Ali (University of Eloued جامعة الوادي, 2023)
The need for energy crops and animal manures for the production of biogas is rising globally. Farmers that raise cattle may use manure as an alternative energy source. Manure is partially converted into energy in the form of biogas by an anaerobic digester. To improve the biogas yield from animal manure must be taken into consideration the quality of manure. It is clear that the difference in the method of pasture has an important impact on biogas production. The study aims to compare the amount of biogas produced from manure animals in barns (closed pastures) and animals in farms (open pastures). The study included different types of manure cows, sheep, and poultry. Experiments were performed in a 2 L plastic bottle digester in a water bath at a 37°C mesophilic range. During the 12-day hydraulic retention period, a mixture of animal dung and water was employed in a 1:1 ratio (HRT). The volumetric water replacement method was used to calculate the amount of gas produced. The results showed that the barn manure had higher biogas production than the farm manure approximately 3 times because their feed had concentrated nutritional supplements
Article
Keywords: Biogas yield; Animal manure; Anaerobic digestion; Method of the pasture; Clean energy.